2014
DOI: 10.1088/0034-4885/77/2/026601
|View full text |Cite
|
Sign up to set email alerts
|

Noise in biology

Abstract: Noise permeates biology on all levels, from the most basic molecular, sub-cellular processes to the dynamics of tissues, organs, organisms, and populations. The functional roles of noise in biological processes can vary greatly. Along with standard, entropy-increasing effects of producing random mutations, diversifying phenotypes in isogenic populations, limiting information capacity of signaling relays, it occasionally plays more surprising constructive roles by accelerating the pace of evolution, providing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
324
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 402 publications
(334 citation statements)
references
References 234 publications
3
324
0
1
Order By: Relevance
“…In recent years, it has been shown that random fluctuations can induce temporal and spatial behaviors that do not exist in the presence of purely deterministic dynamics (44,45). This novel perspective on the significance of randomness has become essential to the environmental sciences, where stochastic components are pervasive (45)(46)(47)(48). Even though noise-driven phenomena such as stochastic resonance, noise-controlled patterning, and noise-enhanced shift precursors have been recently identified in this context, unraveling how environmental fluctuations can cause structural changes in the dynamics is still a largely unexplored subject.…”
Section: Significancementioning
confidence: 99%
“…In recent years, it has been shown that random fluctuations can induce temporal and spatial behaviors that do not exist in the presence of purely deterministic dynamics (44,45). This novel perspective on the significance of randomness has become essential to the environmental sciences, where stochastic components are pervasive (45)(46)(47)(48). Even though noise-driven phenomena such as stochastic resonance, noise-controlled patterning, and noise-enhanced shift precursors have been recently identified in this context, unraveling how environmental fluctuations can cause structural changes in the dynamics is still a largely unexplored subject.…”
Section: Significancementioning
confidence: 99%
“…Therefore, enhancement of cross-talk decreases variability between two kinases in a population. These results imply that cross-talk develops correlated fluctuations between kinases in a population, thereby assisting in the successful development of a robust adaptation machinery as observed in the bet-hedging program under diverse environmental conditions [22]. Here, an increase in the correlation between two different protein pool (with high Pearson's correlation coefficient) is observed for maximal cross-talk.…”
Section: Two Variable Mutual Informationmentioning
confidence: 71%
“…Inter-pathway cross-talk becomes prominent due to the limitation of common resources, defined as the overloaded condition. However, cross-talk effect becomes faint in the underloaded condition, where the level of available resources are present in sufficient amount [19,20,22,24,25]. A key source of survival strategy under diverse environmental conditions is the generation of fluctuations which induces non-genetic variability in a cellular population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we must be aware of the fact that our system is in-part discrete, which means that we rather seek trajectories to the basin of attraction in a cellular automaton as shown by Wuensche [12]. This factor of semi-discretion leads to the positive role of noise in biology [24], which we may briefly describe as a constant faltering of the system, which may more frequently occupy trajectory acquiring a broader part of the phase space.…”
Section: Resultsmentioning
confidence: 99%